Perencanaan Tapak Candi Penampihan untuk Mendukung Pelestarian Sejarah di Kabupaten Tulungagung, Jawa Timur - Safitri, Lina; Yusiana, Lury Sevita; Bawono, Rochtri Agung (Jurnal Arsitektur Lansekap, 2024)
Penampihan Temple Site Planning to Support Historical Preservation Penampihan Temple is a historical element of Hindu religious heritage that was used during the Ancient Mataram Kingdom to the Majapahit Kingdom in the 9-14th century AD in Sendang District. Penampihan Temple has an architectural style and historical value contained in the site which can be a source of knowledge and can foster an appreciation of historical heritage. The development of the Penampihan Temple tourist attraction does not utilize the historical resources of the site optimally and tends to be a tourist destination that is only recreational. The aims of this research are: (1). identify the character and condition of the landscape at the site of Candi Penampihan (2). Planning the site of Penampihan Temple to support historical preservation. The method used in this research is observation, interview, and literature study. Observations are made to find out the conditions or prove the truth of the research being carried out. Interviews were conducted for data collection by conducting direct questions and answers to related parties, the results of the interviews were then used as an approach and data analysis. Literature study is done by comparing the truth of the theory with real events in the field. The results of this research are in the form of a site plan that can support recreational and educational tourism activities to support historical preservation.